Penanggulangan Tindak Pidana Cyberbullying Terhadap Anak Di Indonesia Perspektif Sistem Hukum Lawrence Meir Friedman - Pian, Marlan; Medan, Karolus Kopong; Manafe, Deddy R. CH. (Artemis Law Journal, 2024)
Cyberbullying itself is an extension of the old crime, namely bullying. The difference is, bullying occurs in the real world and is carried out with physical contact between the perpetrator and the victim, while cyberbullying occurs online via electronic media without requiring direct physical contact. However, the impact caused by cyberbullying is proven to be more severe, the victim can experience psychological disorders, not only mental disorders, but also disorders that affect the victim's physical condition. Because digital traces in cyberspace are also difficult to erase, the author conducted this research with the aim of tackling the crime of cyberbullying specifically for children who are victims. Based on this, problems can be formulated: (1) What is the legal system for dealing with cyberbullying crimes against children in Indonesia? (2) What is the legal system for dealing with criminal acts of cyberbullying against children in Indonesia from the perspective of Lawrence Meir Friedman's legal system? This research is doctrinal legal research with research locations in the regional library of East Nusa Tenggara Province. Data obtained using library study techniques. From the research results it was found: (1) The policy for dealing with cyberbullying in criminal law is included in the field of penal policy which is part of criminal policy (crime prevention policy). (2) Countermeasures according to Lawrence Meir Friedman are Legal Structure, Legal Substance, Legal Culture.